1992
DOI: 10.1093/carcin/13.12.2211
|View full text |Cite
|
Sign up to set email alerts
|

Chemical carcinogens and overnutrition in diet-related cancer

Abstract: The intake of known dietary carcinogens was compiled and the cancer risk was estimated on the basis of carcinogenic potencies in animals as derived from the Carcinogenic Potency Database by Gold and co-workers. The total cancer risk was compared with the number of cancer cases attributed by epidemiologists to dietary factors (one-third of all cancer cases, i.e. approximately 80,000 per one million lives). Except for alcohol, the known dietary carcinogens could not account for more than a few hundred cancer cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…The major source of human exposure to environmental PAH contaminants on a daily weight basis is from the diet (64). This exposure pathway is consistent with a large pool of epidemiological data linking the incidence of human cancer (20-50%) and disease with dietary factors (4,10,37,38,56,63,65). Other general and speci c studies have supported this view (38,47,70).…”
Section: Introductionsupporting
confidence: 76%
“…The major source of human exposure to environmental PAH contaminants on a daily weight basis is from the diet (64). This exposure pathway is consistent with a large pool of epidemiological data linking the incidence of human cancer (20-50%) and disease with dietary factors (4,10,37,38,56,63,65). Other general and speci c studies have supported this view (38,47,70).…”
Section: Introductionsupporting
confidence: 76%
“…Evolutionary biologists have argued that aging is inevitable because of several tradeoffs (67)(68)(69)(70) (73)(74)(75)(76). It has been suggested that Darwinian fitness in animals is increased by the delay of reproductive function during periods of low food availability (77) and that the saved resources are invested in maintenance of the body until food resources are available for successful reproduction (78).…”
Section: Aging and Dietary Restrictionmentioning
confidence: 99%
“…It is now well established that genetic factors play a significant role in determining risk for both cancer and coronary heart disease (198,199) and behavioral factors such as cigarette smoking and heavy consumption of alcohol also influence susceptibility to these diseases (199)(200)(201). Nevertheless, when these factors are taken into consideration, dietary caloric consumption may be one of the most important risk factors for a spectrum of human degenerative diseases (4,202), and human epidemiology studies have established that increased body weight-or body mass index (BMI)-is positively correlated to a number of morbidity/mortality indices. These include overall mortality in both men and women (13,203); cardiovascular disease (10,13,204); breast, renal, and endometrial cancer in women (205)(206)(207); and colon cancer in men (208).…”
Section: Influence Of Caloric Intake On Human Morbidity and Mortalitymentioning
confidence: 99%